2022
DOI: 10.1371/journal.pntd.0009848
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of dengue, Zika, chikungunya and Ross River viruses across the Solomon Islands

Abstract: Across the Pacific, and including in the Solomon Islands, outbreaks of arboviruses such as dengue, chikungunya, and Zika are increasing in frequency, scale and impact. Outbreaks of mosquito-borne disease have the potential to overwhelm the health systems of small island nations. This study mapped the seroprevalence of dengue, Zika, chikungunya and Ross River viruses in 5 study sites in the Solomon Islands. Serum samples from 1,021 participants were analysed by ELISA. Overall, 56% of participants were flaviviru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Anti-ZIKV antibodies were found in 66% of the Cook Island test collective and in 52% of the Vanuatu specimens. Refer to [35] for a comparable presentation of a seroprevalence study in the Solomon Islands.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-ZIKV antibodies were found in 66% of the Cook Island test collective and in 52% of the Vanuatu specimens. Refer to [35] for a comparable presentation of a seroprevalence study in the Solomon Islands.…”
Section: Resultsmentioning
confidence: 99%
“…Blue: DENV, orange: ZIKV. Single-color-filled area represents samples that were positive for the respective virus alone; hatched shading indicates samples that were positive for both Flaviviruses (DENV and ZIKV).Refer to[35] for a comparable presentation of a seroprevalence study in the Solomon Islands.…”
mentioning
confidence: 99%
“…Direct detection of dengue cases can be complicated by the fact that (i) dengue infections are often asymptomatic, (ii) when symptomatic, clinical signs and symptoms can be very similar to other arboviruses such as Zika or Chikungunya and (iii) viremia can be short lived or decreasing when symptoms appear, opening only a short window for molecular confirmation [ 56 , 79 , 80 ]. For all these reasons, dengue surveillance is another field in which serology has been informative.…”
Section: Real-life Examples and Public Health Usementioning
confidence: 99%
“…Another study in the Solomon Islands used a cross-sectional survey to detect IgG for four viruses with overlapping symptoms (Dengue, Zika, Chikungunya and Ross River Virus) and to establish their relative burden [ 80 ]. The results showed that Dengue and Ross River Virus had the highest burden on the islands and highlighted the presence of Ross River Virus, even though cases had not been reported prior to the study.…”
Section: Real-life Examples and Public Health Usementioning
confidence: 99%
“…The Solomon Islands is an archipelagic state in the southwest Pacific Ocean just northeast of Australia. Arboviral disease outbreaks (notably dengue) are common in the Solomon Islands, with several significant events affecting the nation in recent years (Cao-Lormeau et al 2014;Darcy et al 2001;Mangum et al 2018;Matthews et al 2022;Nogareda et al 2013;Russell et al 2022). In 2016/17, with 12,329 suspected cases, 877 hospitalisations, and 16 deaths, the Solomon Islands experienced the largest dengue outbreak on record in the Pacific islands (Craig et al 2018b).…”
Section: Introductionmentioning
confidence: 99%